Complementary action of ginger as bioenhancers in the treatment of diabetes - M, Ashoka Shenoy; Mahurkar, Nitin (Indian Journal of Pharmacy & Drug Studies, 2024)
Aim and objective: To evaluate the role of Zingiber officinale extract along with glibenclamide on lipid profile in alloxan & streptozotocin induced diabetes mellitus in rats. Method and Materials: The diabetes in rats was induced by the administration of intraperitoneal injection of alloxan (100mg/kg) and streptozotocin (65 mg/kg). After 2 days of injection, the hyperglycaemic rats (glucose level > 200 mg/dl) were separated and divided into five groups consisting of six rats in each group. The oral treatment was started from the same day for next three weeks. On 21st day the blood was collected for biochemical estimations by retro orbital puncture. The serum was obtained by centrifuging the blood samples at 3000 rpm for 10 m and used for estimation of SGPT, SGOT, SOD and CAT. Results: Diabetic rats treated with glibenclamide and glibenclamide along with ginger extract showed significant (p